2010
DOI: 10.1080/14766081003746448
|View full text |Cite
|
Sign up to set email alerts
|

Money, the meaning of money, management, spirituality, and religion

Abstract: This article briefly summarizes selected theory and research related to money and the meaning of money. Research shows that money is considered as a tool and as a drug. People are subject to all kinds of temptation in the environment that trigger them to act ethically or unethically. Thinking about money enhances one’s feeling of “self‐sufficiency,” but reduces one’s willingness to help others. The mere presence of abundant money incites the feeling of “envy” toward wealthy others that provokes unethical beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
32
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(38 citation statements)
references
References 80 publications
(100 reference statements)
5
32
0
1
Order By: Relevance
“…Females and African-Americans tend to have lower pay than their male and Caucasian counterparts, respectively, in the US. Part-time employees (students) change jobs frequently and are mostly paid at the market value (Tang 2010). Executives must pay employees fairly and reduce their LOM in organizations (Milkovich et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Females and African-Americans tend to have lower pay than their male and Caucasian counterparts, respectively, in the US. Part-time employees (students) change jobs frequently and are mostly paid at the market value (Tang 2010). Executives must pay employees fairly and reduce their LOM in organizations (Milkovich et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Later, Tang, and his associates expanded constructs to include Good/Rich, Motivator, Evil/Unethical, Non-Motivator, Make Money, Budget Money, Donate Money to Charity, Importance, Power, Respect, Achievement, and Equity (Tang 1993(Tang , 2010Tang and Fuller 1995;Tang et al 2005;2006). As expected, ''the love of money'' (Rich, Motivator, Achievement, Respect, Power, and Importance) is related to unethical behavior intention and low life and pay satisfaction.…”
Section: Money Ethicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Tang also revealed that money-based rewards are considered as a powerful motivational trigger [5]. Thus, it can be said that the behavior of individuals can reflect how personal goals and how individuals are in the meaning of money.…”
Section: Discussionmentioning
confidence: 99%
“…Money-based rewards are considered a powerful motivational driver [5]. Other studies have shown that extrinsic factors are often detrimental to desired work attitudes and outcomes (eg, creativity, cognitive flexibility, and problem solving [6].…”
Section: Introductionmentioning
confidence: 99%